(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examines the impact of microfinance bank services on poverty alleviation in rural Nigeria, addressing the alarming poverty rate, with 63% of Nigerians experiencing multidimensional poverty—72% in rural areas. Using a mixed-method approach, data were collected through questionnaires and focus group discussions (FGDs) from 105 respondents, employing stratified and simple random sampling. A community-based cross-sectional survey was conducted, and data were analyzed using Chi-square (X²). The result of the analyzed data portrayed that microfinance banks’ services measured in terms of socio-economic wellbeing, people’s access to credit facilities, and sustainable poverty alleviation is significantly associated with the services of microfinance banks in rural communities in Nigeria. Based on these findings, it was recommended among others that there should be sustainable refinancing arrangement which is the only sure way to guarantee microfinance banks to move their most vulnerable clients above the poverty line. There should be change in credit focus –diversification to pursue the microfinance banks core objectives with a consistent as well as concerted efforts to reach the target of microfinance banks. Besides, there should be need for massive awareness creation of microfinance banking in terms of what it is, what it is not, as well as its gains and development potentials to extricate the poor in rural communities in Nigeria from the courage of poverty.